English sentence constructions - Verspoor, Marjolyn (John Benjamins Publishing Company, 2022)
"English Sentence Constructions departs from a usage-based theoretical perspective in which all language units -- which we refer to as constructions -- have both a meaning and form, and context is all-important in determining the function and form of these constructions. As a starting-level module, English Sentence Constructions guides students of English or Language at tertiary level through different levels of analysis at the sentence, clause, phrase, and word level. The book starts with an explanation of different sentence types and structures (Chapters 1 and 2), zooms in on the verb phrase as the central component of any sentence (in Chapters 3 and 4), before zooming in even closer, discussing word classes (Chapter 5) and phrases (Chapter 6). The next two chapters explicate the intricacies of sentence constituents that function as clauses (Chapter 7) and aid students in integrating all chapters by discussing sentence analysis at all levels (Chapter 8). The last chapter (Chapter 9) shows how knowledge about sentence constructions can be applied to effective writing in English. English Sentence Constructions can be used in teacher-led modules, but the many exercises in the chapter, the clearly worked out answer keys, and a comprehensive glossary of terminology also make it suitable for self-study. For each chapter, there is an online test in which students can check their understanding"--